2020
DOI: 10.3390/metabo10020063
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Is the Key to the Antidepressant Effect of Chaihu-Shu-Gan-San

Abstract: Accumulating evidence highlights the link between gut microbiota and depression. As an antidepressant herbal drug in clinic, Chaihu-Shu-Gan-San (CSGS) has also been used in China for the treatment of various gastrointestinal disorders. Therefore, we hypothesize that the gut microbiota might be involved in the effect of CSGS. Here, we investigated the antidepressant effects of CSGS against chronic variable stress (CVS)-induced depression rats with and without antibiotic treatment using 16S rRNA gene sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Liang et al reported that CSS suppressed the Enterobacteriaceae population in the feces of rat with high fat diet-induced obesity [ 19 ]. However, Yu et al reported that chronic exposure to imipenem/cilastatin increased Proteobacteria and Bacteroidetes populations and suppressed the Firmicutes in the gut microbiota of rats [ 20 ]. They also reported that oral gavage of CSS alleviated stress/antibiotics-induced depression in rats by suppressing stress/antibiotics-induced Oscillibacter population and increasing stress/antibiotics-suppressed Bacteroidetes population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liang et al reported that CSS suppressed the Enterobacteriaceae population in the feces of rat with high fat diet-induced obesity [ 19 ]. However, Yu et al reported that chronic exposure to imipenem/cilastatin increased Proteobacteria and Bacteroidetes populations and suppressed the Firmicutes in the gut microbiota of rats [ 20 ]. They also reported that oral gavage of CSS alleviated stress/antibiotics-induced depression in rats by suppressing stress/antibiotics-induced Oscillibacter population and increasing stress/antibiotics-suppressed Bacteroidetes population.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al reported that the induction of Proteobacteria, particularly Enterobacteriaceae, by antibiotic ampicillin significantly caused anxiety/depression in mice and the suppression of Proteobacteria by Lactobacilli alleviated anxiety/depression [ 21 ]. However, Yu et al reported that CSS increased stress/antibiotics-suppressed Firmicutes and Proteobacteria populations in mice, resulting in the amelioration of depression [ 20 ]. To clarify the discrepancy, we examined the fecal transplantation of FN, FR, and FC in mice with RS-induced depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antidepressant treatment was also found to influence the gut microbiome in MDD patients, with greater microbiome diversity in those patients exhibiting remission (Bharwani et al., 2020). Interestingly, broad‐spectrum antibiotic treatment reversed the antidepressant effects of a Chinese herbal drug and also suppressed serotonin and glutamic acid levels in the rat hippocampus (Yu et al., 2020). Antibiotic treatment also reversed the beneficial effect of the drug in improving Lactobacillus numbers and caused gut dysbiosis and reduced gut microbiome diversity.…”
Section: Physiological Factors That Play Key Roles In the Comorbiditymentioning
confidence: 99%
“…Fluoxetine ( Lukic et al., 2019 ; Sun et al., 2019 ), ketamine ( Qu et al., 2017 ), escitalopram, and duloxetine ( Lukic et al., 2019 ) can improve depressive and anxiety-like behaviors and are associated with alterations in gut microbiota composition. It was recently reported that the downregulation of inosine in the hippocampus of rats caused by depression was corrected after treatment with traditional Chinese medicine, and that these variations in inosine were eliminated after antibiotic intervention ( Yu et al., 2020 ). The serum metabolite level of inosine was restored by Lactobacillus treatment in mice with gut microbial dysbiosis ( He et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%